GRAVES’ DISEASE COMPLICATED WITH THYROID STORM AND SEVERE CHOLESTASIS - Low, Chee Kon; Wong, Hui Chin; Nesaratnam, Shalena; Shahar, Hamiza; Yong, Sy Liang (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION A multifaceted relationship exists between the thyroid gland and the liver, which is crucial for maintaining homeostasis. Therefore, it is common to identify liver dysfunction in patients with thyroid disease. Although cholestasis can be associated with thyroid storm, it is important to ascertain the etiology as other conditions such as drug-induced cholestasis, autoimmune liver disease and sepsis-related hepatic dysfunction warrant specific management. CASE We report a case of severe cholestasis in a patient presenting with thyroid storm secondary to Graves’ disease in whom heart failure and other secondary causes were appropriately investigated. We also present other relevant reports and studies available in the literature. A 39-year-old female presented with jaundice, symptoms of thyrotoxicosis and heart failure. Clinically, she had exophthalmos with a moderately enlarged thyroid and signs of heart failure. Burch-Wartofsky Point Scale was 70. Her thyroid-stimulating hormone level was suppressed at 0.02 mU/L, with high free thyroxine of 92.4 pmol/L and free triiodothyronine of more than 30.8 pmol/L. She also had hyperbilirubinaemia which was predominantly conjugated, mildly elevated aspartate transaminase (AST) of 86 IU/L and normal alanine transaminase (ALT) level of 34 IU/L. Blood parameters were prolonged with activated partial thromboplastin time (APTT) of more than 180 seconds and international normalized ratio (INR) of 2.14. She was commenced on Lugol’s iodine, corticosteroids and propranolol for thyroid storm, ursodeoxycholic acid for cholestasis and furosemide along with spironolactone for heart failure. She improved gradually and was discharged after a month of hospitalization. CONCLUSION Severe cholestasis in patients with thyrotoxicosis is a common presentation and may dominate the clinical picture of the primary disease. The recognition of liver and cardiac complications of thyrotoxicosis together with a thorough evaluation for other etiologies will allow proper management and hence, steady improvement of this serious medical condition.